Gamification proposal for defect tracking in software development process (2016)
Software process improvement is an approach used by software industries to increase the productivity and quality of their processes and products. One important issue is the social interaction among the team members looking for productivity enhancement, motivation and training, among others. However, these social skills are difficult to train in a traditional way both in academic and industrial environments. This difficulty could be address-using gamification like a strategy to improve the social factors related to the software development process. In this paper, we present a gamification proposal focused on training in defect tracking. This training looks for evaluation, implementation and use of a pedagogical instrument (game) for train in defect tracking practices following the principles of gamification. Additionally this instrument promotes other skills like teamwork, negotiation and effective communication.